2008
DOI: 10.1090/conm/464/09080
|View full text |Cite
|
Sign up to set email alerts
|

Sums and products in finite fields: an integral geometric viewpoint

Abstract: We prove that if A ⊂ F q is such that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
79
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(84 citation statements)
references
References 10 publications
5
79
0
Order By: Relevance
“…On the other hand, we show that our approach also gives an alternative proof of the corresponding results of [9] and [18] for available at https://www.cambridge.org/core/terms. https://doi.org/10.1017/S0017089508004382…”
Section: Possible Improvementssupporting
confidence: 57%
See 3 more Smart Citations
“…On the other hand, we show that our approach also gives an alternative proof of the corresponding results of [9] and [18] for available at https://www.cambridge.org/core/terms. https://doi.org/10.1017/S0017089508004382…”
Section: Possible Improvementssupporting
confidence: 57%
“…which leads to (9). We remark that in a recent work of Garaev [5] considering equation (6) (for some special sets A, B, C, D) has been the main tool in obtaining new results on the sumproduct problem in finite fields (see also [2-4, 9, 11, 15, 16]).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Bourgain [2005] showed that for A ⊆ ‫ކ‬ q such that |A| q 3/4 , one has A · A + A · A + A · A = ‫ކ‬ q ; in particular, if |A| ≈ q 3/4 , then |A · A + A · A + A · A| |A| 4/3 . In [Hart and Iosevich 2008] it was shown that if |A| q 3/4 , then A · A + A · A = ‫ކ‬ * q ; in particular, if |A| ≈ q 3/4 , then |A · A + A · A| |A| 4/3 . Due to the misbehavior of the zero element, it is not possible to guarantee that A · A + A · A = ‫ކ‬ q unless A is a positive proportion of the elements of ‫ކ‬ q .…”
Section: Introductionmentioning
confidence: 99%